2022
DOI: 10.1186/s12889-022-14101-z
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Chinese ABCD risk questionnaire to evaluate adults’ awareness and knowledge of the risks of cardiovascular diseases

Abstract: Background Assessment of health beliefs and risk perception is a critical means to prevent coronary heart disease, but there are few such studies on assessment in the Chinese population. Given the demonstrated value and widespread use of the Attitudes and Beliefs about Cardiovascular Disease Risk Questionnaire (ABCD), this study was designed to translate it into Chinese, and to evaluate its reliability and validity in a Chinese population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The ABCD scale was developed by Woringer et al based on the Health Belief Model and the Transtheoretical Model to assess CVD risk perception. 26 It was translated and revised by Liu et al, who then produced a Chinese version with the following four dimensions containing 27 items: CVD knowledge, perception of risks, perception of benefits, and healthy eating intention 27. The dimension of knowledge was measured using a dichotomous response option (yes/no questions), while the other three dimensions were measured using a 5-point Likert scale (1 “completely disagree” to 4 “completely agree”).…”
Section: Methodsmentioning
confidence: 99%
“…The ABCD scale was developed by Woringer et al based on the Health Belief Model and the Transtheoretical Model to assess CVD risk perception. 26 It was translated and revised by Liu et al, who then produced a Chinese version with the following four dimensions containing 27 items: CVD knowledge, perception of risks, perception of benefits, and healthy eating intention 27. The dimension of knowledge was measured using a dichotomous response option (yes/no questions), while the other three dimensions were measured using a 5-point Likert scale (1 “completely disagree” to 4 “completely agree”).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection was undertaken between 20 September 2022 and 13 June 2023. We used the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist [33] as guidelines to ensure the reporting quality of the present study (see S1 shown excellent reliability and strong validity in the general population of Chinese adults [35]. In the present study, our sample had Cronbach's alpha values of 0.92.…”
Section: Participants and Settingsmentioning
confidence: 99%